Hydrogels with reversible stiffness modulation: new materials for studying dynamic mechanical cues that regulate cell behavior - Li, Pinxue; Liu, Yubo; Liu, Shuaiyi; Zhou, Meng; Wang, Xing; Yu, Fangyuan (Frontiers in Bioengineering and Biotechnology, 2025)
As the fundamental environment for cell survival, the extracellular matrix (ECM) not only serves as the substrate for cell function and structure formation but also guides cell activities through its dynamic physical properties. Therefore, the relationships by which the physical and mechanical properties of the ECM guide cell behavior such as growth, development, differentiation and reproduction are important to understand. Because substrate stiffness is an important physical property that influences cell behavior, this paper focuses on the relationship between stiffness and cell behavior. Hydrogels, as networks of hydrophilic polymer chains, are an excellent model for the physical properties of the ECM in cellular studies due to its multiple similarities with the ECM. This review classifies hydrogels in terms of their origin and their relative stiffness and presents an overview of their formation, properties, regulation, and applications. We believe that hydrogels with variable elastic moduli will continue to be of considerable use in future studies to further elucidate the effects of mechanical cues on cell behavior.